Study Some Properties of Solar Cell Fabricated by Deposited Cadmium Oxide on Pours Silicon in Three Different Temperatures - Mahdi, Raghad R.; Maki, Samier A.; AL Salihi, Hind A.; Abood, Marwa K.; Halbos, Raghad J.; Hassan, Ruqia Abdulhussien; Fayad, M. A. (Peneliti Teknologi Teknik Indonesia, 2024)
In this research cadmium oxide were prepared by using the chemical simple method, and a pours silicon has been fabricate by using the etching technique on the regular silicon, a solar cell is fabricated by deposited the cdo on the prepared pours silicon (Cdo/Psi) by the drop casting method and do the annealing process in three deferent temperatures (200,400,600) c˚. The XRD testes show that all the prepared samples are poly crystalline and cubic with orientations peaks (111,101,100,102). The optical testes show that these thin films have a high absorbency and low transmittance decrease with increasing the annealing temperature. The short circuit current (Isc) and the short circuit voltage (Vsc) of the fabricated solar cell showed that the conversion efficiency increase as the annealing process temperature increase until it become (9.3)% at (600)c˚.